Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0300891619847085
|View full text |Cite
|
Sign up to set email alerts
|

Development, technical validation, and clinical application of a multigene panel for hereditary gastrointestinal cancer and polyposis

Abstract: Introduction: Recent advances in technology and research are rapidly changing the diagnostic approach to hereditary gastrointestinal cancer (HGIC) syndromes. Although the practice of clinical genetics is currently transitioning from targeted criteria-based testing to multigene panels, important challenges remain to be addressed. The aim of this study was to develop and technically validate the performance of a multigene panel for HGIC. Methods: CGT-colon-G14 is an amplicon-based panel designed to detect single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The genes with pathogenic variations were MUTYH (*604933), PALB2 (*610355), ATM (*607585), MLH1 (*120436), MSH2 (*609309), BRCA1 (*113705), APC (*611731), NBN (*602667), CHEK2 (+604373), RECQL3 (*604610), and FLCN (*607273); the genes with VUS were PMS2 (*600259), TSC2 (*191092), EP300 (*602700), GATA3 (*131320), NBN (*602667), EXT2 (*608210), AXIN2 (*604025), CHEK2 (+604373), MUTYH (*604933), ERBB2 (*164870), and BRCA2 (*600185). In a similar study including 48 cases of CRC/polyposis syndrome, Ricci et al 28 reported 23 pathogenic/likely pathogenic variations and 22 VUS in 14 different genes. The genetic heterogeneity of CRC syndromes indicates that multigene analyzing systems are cost- and time-effective for diagnosis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The genes with pathogenic variations were MUTYH (*604933), PALB2 (*610355), ATM (*607585), MLH1 (*120436), MSH2 (*609309), BRCA1 (*113705), APC (*611731), NBN (*602667), CHEK2 (+604373), RECQL3 (*604610), and FLCN (*607273); the genes with VUS were PMS2 (*600259), TSC2 (*191092), EP300 (*602700), GATA3 (*131320), NBN (*602667), EXT2 (*608210), AXIN2 (*604025), CHEK2 (+604373), MUTYH (*604933), ERBB2 (*164870), and BRCA2 (*600185). In a similar study including 48 cases of CRC/polyposis syndrome, Ricci et al 28 reported 23 pathogenic/likely pathogenic variations and 22 VUS in 14 different genes. The genetic heterogeneity of CRC syndromes indicates that multigene analyzing systems are cost- and time-effective for diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…Ricci et al 28 studied 14 genes in 48 hereditary gastrointestinal cancer and polyposis cases and 23 pathogenic/likely pathogenic variations and 22 VUS were detected. In our study, 30 (37.5%) pathogenic/likely pathogenic variations, 19 (23.75%) VUS, and 4 (5%) deletions were detected with MLPA; the mostly pathogenic/likely pathogenic variations were on the MSH2 gene with the diagnosis of colon cancer/colon cancer family history or Lynch syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were selected from the TEAD registry. The inclusion criteria for patients were (1) having an identified pathogenic variant in a gene responsible for gastrointestinal cancer predisposition syndromes such as APC, MUTYH, POLE, SMAD4, MLH1, MSH2, MSH6, PMS2 , or CDH1 [ 14 ]; (2) providing written consent for research purposes; (3) being under active follow-up; (4) being ≥ 18 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…For all patients, a colorectal polyposis was endoscopically excluded and a negative family history for CRC/polyps was assessed. Additionally, in order to further exclude gastrointestinal cancer predispositions, we performed genetic testing with a multigene panel in all available PED patients (five out of eight) that resulted not-informative in all of them 32 .…”
Section: Patient Cohortmentioning
confidence: 99%